Pattern Recognition: Using Rocks, Wind, Water, Anxiety, and Doom Scrolling in a Slow Apocalypse (to Learn More About Methods for Changing the World). (September 2021) - Markham, Annette N.
In 5 months of COVID isolation, living out of a suitcase in temporary housing, countless fractal patterns emerged. I can't say if I created these patterns by looking for them, or that I know the whole world by looking at a grain of sand. The truth of the matter is that it feels like the key for massive scale change is just in front of us, but slipping from our grasp. As we move through these days, weeks, and months, we have very little time before the difference recedes again. I address this matter of concern as a matter of method in performative grounded theory piece.